2019
DOI: 10.48550/arxiv.1908.00649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locally finitely presented and coherent hearts

Abstract: Given a torsion pair t = (T , F ) in a Grothendieck category G, we study when the heart H t of the associated Happel-Reiten-Smalø t-structure in the derived category D(G) is a locally finitely presented or a locally coherent Grothendieck category. Since H t is Grothendieck precisely when t is of finite type (i.e., F is closed under direct limits), we first study the latter torsion pairs showing that, as in modules, they are precisely the quasi-cotilting ones, that in turn coincide with the cosilting ones.We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The canonical finitely accessible subcategory of a Grothendieck category. The following is an extended version of [26,Lemma 1.11]. Proposition 9.16 (Generalized Lazard's Trick).…”
Section: The Subcategory Gen(fg(a)) Whenmentioning
confidence: 99%
“…The canonical finitely accessible subcategory of a Grothendieck category. The following is an extended version of [26,Lemma 1.11]. Proposition 9.16 (Generalized Lazard's Trick).…”
Section: The Subcategory Gen(fg(a)) Whenmentioning
confidence: 99%
“…We apply an argument due to Lazard (see [PSV21,Lem. 1.11]), that we just outline here, to show that T ∈ lim − → pres(V ).…”
Section: / / Special Precovering Torsion-free Classes In Amentioning
confidence: 99%
“…Remark 6.10. In [PSV21] (see the discussion right after Proposition 8.19 in [Op.Cit. ]), we have shown that the answer to the above question is negative when Mod-R is replaced by a locally coherent Grothendieck category.…”
Section: / / Special Precovering Torsion-free Classes In Amentioning
confidence: 99%
“…i.e., by definition of Yoneda ext-group, there is an index γ ∈ Λ such that ξ i factors as the pushout diagram (see again [PSV19] for details)…”
Section: A Criterion For the Local Coherencementioning
confidence: 99%
“…On the other hand, crucial results concerning the finiteness conditions have been achieved e.g. in [Sao17,PSV19]. An exhaustive survey devoted to the study of HRS hearts and related topics is [PS20].…”
Section: Introductionmentioning
confidence: 99%